„Album Orbis" [III] Cypriana Norwida - struktura opowieści - struktura dziejów - Jaworska, Anna (Przestrzenie Teorii, 2008)
It is just Cyprian Norwid's Album Orbis, a work "in sketch", also called by him "an artistic wallet" but also "a collection of motifs" encompassing the whole course of civilisation of the world could be an attempt at capturing "the whole", revealing the vastness of creative powers of an artist-conjurer. Norwid reveals before the spectator both the spectacle of civilisation as well as the depth of epochs in which the time of history is concealed and through this forces one to confrontation with the remains of the past, pulled out from the memory and stuck in his Album Orbis. The discovery of the places where particular parts are connected is not easy, however, if one of them is found, the elements which are apparently alien to each other begin to create one tale. Creation of history appears to be possible only when time threshold is crossed, when the past, the future and the present concentrate on a particular picture, word, thought.